Model Countermeasures Children which Commit Crimes in Review Restorative Justice - Kaimudin, Arfan; Ashsyarofi, Hisbul Luthfi (Jurnal Cakrawala Hukum, 2023)
This study describes the model settlement of cases through non-penal channels for crimes committed by children according to Act 11 of 2012 concerning the Juvenile Criminal Justice System with prioritizing restorative justice so that children who commit crimes are not stigmatized negatively. The Juvenile Criminal Justice System concept has included solving problems in a family manner or for children in conflict with the law, formally known as diversion. Diversion exists to divert the settlement of child cases from the criminal justice process to processes outside criminal justice. Diversion exists to prevent children who conflict with the law from the negative impacts of the criminal justice process on children. United Nations Standard Minimum Rules for the Administration of Juvenile (The Beijing Rules) have provided guidelines to prevent children in conflict with the law from negative impacts, namely by giving law enforcers the authority to take action in handling or resolving the problems the child offenders by not taking courts, among others stopping or not continuing or releasing or returning or handing over to society and other forms of social service activities. How to cite item: Kaimuddin, Arfan, and Hisbul Luthfi Ashsyarofi. â€œModel Countermeasures Children Who Commit Crimes in Review Restorative Justice.â€ Jurnal Cakrawala Hukum 14 no. 2(2023): 134-145. DOI: 10.26905/v14i2.10783.